Optimalisasi Pembelajaran Bahasa Inggris Melalui Pelatihan Guru SD Tentang Pemanfaatan Media Digital Dan AI Di SDN 1 Labu Api, Kecamatan Labu Api - Bafadal, Moh Fauzi; Muhammad Hudri; Ilham; Sofia Dwi Sanzain (Universitas Mataram, 2025)
This community service program aims to improve the quality of English language learning in elementary schools through training in the use of digital media and artificial intelligence (AI) for teachers at SDN 1 Labu Api, West Lombok. The program was initiated due to the limited use of digital media and AI in English language teaching, which has resulted in low student engagement and learning effectiveness. Activities include needs analysis, intensive training, classroom mentoring, and program evaluation. Teachers are introduced to various platforms such as Canva, Quizizz, YouTube Edu, Duolingo, and ChatGPT to improve teaching practices and student engagement. Evaluation results show a significant increase in digital literacy, confidence, and teachers' ability to create interactive teaching materials. Post-training observations revealed a shift toward more innovative and technology-integrated teaching methods. The program also fostered a collaborative culture among teachers and sparked sustainable changes in classroom dynamics. Overall, this initiative contributed to empowering teachers as agents of digital transformation in basic education. Translated with DeepL.com (free version)